Corrosion Resistance Test Using Gravimetric Method on Fuel Tanks of Ethanol Fuel Vehicles - Muji Setiyo; Saifudin Saifudin; Abdul Wahid Jamin; Rifqi Nugroho; Muhammad Rizal Ibrahim (Jurnal Teknik Mesin (JTM), 2017)
In the next few decades, ethanol will take on the role of replacing fossil fuels. However, for direct application to the existing vehicles, an assessment of the corrosion resistance of the fuel tank is required. Therefore, this paper presents the results of corrosion resistance investigation of fuel tanks due to the application of ethanol. A Gravimetric method is used to test the corrosion. Ethanol is mixed with NaCl at various percentages as a corrosive medium. The test results show that the fuel tank has good resistance to corrosion due to ethanol use.